การพัฒนาทักษะในด้านการอ่านสะกดคำโดยใช้ชุดแบบฝึกอ่านของนักเรียนชั้นประถมศึกษาปีที่ 5 โรงเรียนบ้านกุดจอกห้องพอกขี้เหล็ก ตำบลน้ำคำใหญ่ อำเภอเมือง จังหวัดยโสธร - แสงชาติ, อัจฉราภรณ์; ปโยโค, พระมหาจิรายุทธ; ทองใบ, จิรัชญา (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 1 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 1 : มกราคม - เมษายน 2568, 2025)
This research aims to examine the factors contributing to difficulties in Thai pronunciation, explore strategies for enhancing Thai pronunciation skills, and develop guidelines to promote the improvement of Thai pronunciation skills among Grade 5 students at Ban Kut Jok Hong Pok Khee Lek School, Nam Kham Yai Subdistrict, Mueang District, Yasothon Province. The target group for this study consists of five Grade 5 students in the first semester of the 2024 academic year. The research employs a quasi-experimental design. The findings reveal that the Grade 5 students at Ban Kut Jok Hong Pok Khee Lek School in the first semester of the 2024 academic year exhibited a moderate level of proficiency (m = 3.03, s = 0.79). Additionally, the students’ ability to read complex words was also found to be at a moderate level (m = 3.03, s = 0.79), aligning with the 80/80 criterion.